Alleviating symptoms of paediatric acute rhinosinusitis and acute otitis media with otorrhea using nasal-spraying Bacillus probiotics: a randomized controlled trial - Thanh Huu Khieu; Dung Phuong Le; Binh Thanh Nguyen; Binh Thanh Ngo; Hong Thi Chu; Duc Minh Truong; Hung Minh Nguyen; Anh Hoa Nguyen; Tung Dinh Pham; Anh Thi Van Nguyen (Scientific Reports)
Abstract Acute rhinosinusitis (ARS) in children may be accompanied by acute otitis media (AOM) which is often associated with bacterial co-infections. These conditions are among the primary reasons that children visit hospitals and require antibiotic treatment. This study evaluated the efficacy of the nasal-spraying probiotics (LiveSpo Navax containing 5 billion Bacillus subtilis and B. clausii spores/5 mL) as a supportive treatment for dual ARS and AOM with otorrhea in a randomized, single-blind, controlled clinical trial. Eighty-two patients (41 per group), aged 1 month to 12 years, received standard care along with nasal spraying of either physiological saline (Control group) or LiveSpo Navax (Navax group), administered three times daily over a 7-day follow-up period. A total of sixty-one patients (30–31 per group) completed the trial. The Navax group experienced 68.00% and 96.77% reductions in nasal congestion (by day 3) and rhinorrhea (by day 7), respectively, which were 2.04 and 1.94-fold higher than the Control group, with odds ratios (OR) of 4.31 and 30.00 (p < 0.05). Endoscopic results indicated 8% and 11% higher reductions in nasal mucopurulent discharge and tympanic membrane hyperemia in the Navax group compared to the Control group. By day 3, compared to day 0, the Navax group exhibited > 1200-fold reduction in Streptococcus pneumoniae and ≥ 4-fold reduction in Haemophilus influenzae concentrations (p < 0.05) in both nasopharyngeal and middle ear fluid samples, whereas the Control group showed no significant reductions. Navax treatment reduced IL-6 by 1.35- to 1.74-fold and TNF-α by 1.17- to 1.45-fold, more effectively than the Control group (p < 0.05). These results suggest that nasal-spray Bacillus spore probiotics, with their ability to reduce bacterial load and modulate immune responses, provide a cost-effective and safe solution for alleviating symptoms of both ARS and AOM in children. Trial registration: ClinicalTrials.gov, Identifier NCT05804123 on April 7, 2023.